Correlation Between Iron Status And Blood Pressure With Nitric Oxide (NO) Levels Of Pregnant Women In Semarang City, Indonesia - Rahfiludin, Mohammad Zen; Pangestuti, Dina Rahayuning; Suyatno; Suroto (International Journal of Psychosocial Rehabilitation, 2020)
Cases of pregnant women’s death are still high, and most are caused by bleeding and hypertension. However, studies that prove the relationship of iron status and blood pressure with Nitric Oxide levels for pregnant women are still limited. This study aims to analyze the relationship between hemoglobin level, serum transferring receptor (sTfR), and blood pressure with nitric oxide level in pregnant women. This study used a cross-sectional design. Subjects were 79 pregnant women in their third trimester in Semarang City, Central Java Province, Indonesia. Hemoglobin level was measured with cyanomethamoglobin meanwhile serum transferring receptor, and NO was measured with ELISA method. Data were analyzed with rank spearman. Study results reveal that the median of hemoglobin level was 11.30 g/dl, the median of sTfR was 15.06 nmol/l, and the median of NO was 63.69 nmol/l. There were no correlation between NO with hemoglobin level (p=0.776; r=0.033) and sTfR (p=0.568; r= -0.065). There was an inverse correlation between NO and systolic blood pressure (p= 0.014; r= -0.276), however there was no significant correlation between NO and diastolic blood pressure (p= 0.060; r= -0.212). There was a significant difference in the NO level between pregnant women with normal blood pressure and hypertension. Among several variables studied, NO levels are only correlated with systolic blood pressure.